Durability, Intuition, and Vision in Bergson's Philosophy - حسن, زينب (Latakia University Journal - Arts and Humanities Sciences Series, 2025)
Research Methodology:The intellectual methodology in this research will combine both rational and historical approaches aimed at defining the concepts and ideas presented by Bergson and deducing what is beneficial. Our choice of the historical method intends to trace Bergson's concepts back to their original sources, seeking to determine the spirit to which they belong by returning to their French roots. Conclusions and Recommendations:This research aims to shed light on one of the most significant contemporary philosophies, not only in the context of French philosophy but in the broader scope of modern philosophy as a whole. We have attempted to clarify the intricate relationship between vision, durability, and time. When Bergson discusses the concepts of vision and intuition, he embodies them with meanings and implications that are inexhaustible and constantly evolving, reflecting new meanings consistent with the spirit of the era in which the vision is defined, striving to express itself through a wide array of concepts that the philosopher innovates. These concepts serve as precise articulations of the problems he encounters and works diligently to address while proposing suitable solutions. Hence, Bergson endeavored to outline the features of what he called the vision method, ensuring it aligns with the evolutionist doctrine amidst the intense debates involving philosophers and scientists within the French cultural milieu, who were categorized under three philosophical currents: the spiritual current, the vital current, and the evolutionary current.